2021
DOI: 10.2174/1567205018666210218162856
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane But Not Propofol Provided Dual Effects of Cell Survival in Human Neuroblastoma SH-SY5Y Cells

Abstract: Background: We have hypothesized that the most commonly used intravenous (propofol) and inhalational (sevoflurane) general anesthetics affect cell survival concentration and duration dependently with different potency associated with their differential potency to affect intracellular calcium homeostasis. Methods: Human neuroblastoma SH-SY5Y cells stably transfected with either wild type or M146L mutant human presenilin 1 were cultured and exposed to equipotent of propofol or sevoflurane. Cell viability, cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Also, Müller‐Edenborn et al 30 found that SEV slows down colon cancer progression in vitro by inhibiting MMP9. Recently, Gao et al 31 found that SEV (but not propofol) promoted the survival of human NB SH‐SY5Y cells at clinically relevant concentrations and durations. However, 1% SEV caused significant cell damage after its prolonged exposure (24 h) 31 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Also, Müller‐Edenborn et al 30 found that SEV slows down colon cancer progression in vitro by inhibiting MMP9. Recently, Gao et al 31 found that SEV (but not propofol) promoted the survival of human NB SH‐SY5Y cells at clinically relevant concentrations and durations. However, 1% SEV caused significant cell damage after its prolonged exposure (24 h) 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Gao et al 31 found that SEV (but not propofol) promoted the survival of human NB SH‐SY5Y cells at clinically relevant concentrations and durations. However, 1% SEV caused significant cell damage after its prolonged exposure (24 h) 31 . We hypothesized that SEV also repressed NB in view of its inhibitory properties in various tumour cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations